Enantioselective synthesis of (+)-alpha-conhydrine and (-)-sedamine by L-proline-catalysed alpha-aminooxylation - Shaikh, Tanveer Mahamadali; Sudalai, Arumugam (European Journal of Organic Chemistry, 2010)
An efficient organocatalytic approach to the enantioslective synthesis of two important piperidine alkaloids, namely (+)-alpha-conhydrine (98% ee) and (-)-sedamine (95% ee), by L-proline-catalysed alpha-aminooxylation of aldehydes has been developed. The strategy involves an intramolecular cyclization to construct the piperidine core.
Keywords: alkaloids; Amino acids; Aminooxylation; Enantioselectivity; organocatalysis